Consequences of Routine Work-Schedule Instability for Worker Health and Well-Being - Schneider, Daniel; Harknett, Kristen (American Sociological Review, 2019)
Research on precarious work and its consequences overwhelmingly focuses on the economic dimension of precarity, epitomized by low wages. But the rise in precarious work also involves a major shift in its temporal dimension, such that many workers now experience routine instability in their work schedules. This temporal instability represents a fundamental and under-appreciated manifestation of the risk shift from firms to workers. A lack of suitable existing data, however, has precluded investigation of how precarious scheduling practices affect workers’ health and well-being. We use an innovative approach to collect survey data from a large and strategically selected segment of the U.S. workforce: hourly workers in the service sector. These data reveal that exposure to routine instability in work schedules is associated with psychological distress, poor sleep quality, and unhappiness. Low wages are also associated with these outcomes, but unstable and unpredictable schedules are much more strongly associated. Precarious schedules affect worker well-being in part through the mediating influence of household economic insecurity, yet a much larger proportion of the association is driven by work-life conflict. The temporal dimension of work is central to the experience of precarity and an important social determinant of well-being.